2012
DOI: 10.1177/039463201202500326
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Debridement Plus Topical Cyclosporine a in the Treatment and Vernal Shield Ulcers

Abstract: Vernal keratoconjunctivitis (VKC) is a severe chronic bilateral inflammation of the ocular surface characterized by seasonal exacerbations. Long-term prognosis is generally good; however, 6% develop sequelae responsible for permanent visual impairment. Corneal involvement is almost always present, consisting of punctate keratitis, shield ulcers (3-11%) and late corneal neovascularization. In recent years, topical cyclosporine A preparations at 2% in oil or at 1% in polyvinyl alcohol, have been successfully pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The remaining 13 records were evaluated in full-text form. Of these, 10 full-text articles were deemed eligible for our systematic review [11][12][13][14][15][16][17][18][19][20]. Figure 1…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…The remaining 13 records were evaluated in full-text form. Of these, 10 full-text articles were deemed eligible for our systematic review [11][12][13][14][15][16][17][18][19][20]. Figure 1…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…According to the ocular involvement, VKC is classified as tarsal VKC, characterized by giant cobblestone papillae in the upper tarsal conjunctiva, or limbal/bulbar VKC, characterized by gelatinous opacification at limbus with Horner-Trantas dots. Corneal involvement is present in most cases, ranging from mild epithelial keratopathy to plaque ulcers 3 potentially leading to permanent sequelae such as visual impairment. [4][5][6] The etiology of VKC is still unknown, but both immunoglobulin E (IgE)mediated and non-IgE-mediated mechanisms are implicated.…”
mentioning
confidence: 99%
“…Although we have presented only two cases, few studies to date have discussed the advantages of excision of shield ulcers to interrupt the course of the disease. A database search in PubMed, ScienceDirect, Scopus, Google Scholar, SciELO, and LILACS yielded the following articles on the subject (in chronological order): Solomon et al [12], Ozbek et al [8], Fukuda et al [13], Caputo et al [14], Reddy et al [5], Mushtaq et al [9], Cameron [15], and Das [16] ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by Ozbek et al [8], Fukuda et al [13], Mushtaq et al [9], and Das [16] were excellent. Caputo et al [14] found that, among 700 children under treatment, four developed shield ulcers, and they all experienced good disease resolution after plaque removal. Excimer laser phototherapeutic keratectomy was employed as an auxiliary treatment in three eyes with shield-shaped corneal ulcers and plaques caused by vernal keratoconjunctivitis [19].…”
Section: Discussionmentioning
confidence: 99%